Glossing and L2 vocabulary learning through dynamic instruction in the context of Primary Education - Gema Alcaraz Mármol (Revista de Lingüística y Lenguas Aplicadas)
The present study deals with two types of L2 glosses, namely dynamic and traditional text-based glosses. The former were presented to students as a set of prompts designed to help learners identify the correct keyword, whereas the latter were introduced as traditional annotations containing L1 equivalents. A third control group was included in the study. Particularly, the focus is to compare the effects of these two types of glosses in Primary Education students of EFL. During the treatment session the dynamic glossing and the traditional glossing groups were presented three short texts with some unknown words. After the treatment, the three groups were tested in terms of both receptive and productive knowledge of the unknown words. Testing was carried out immediately and some weeks after the treatment. The results of immediate and delayed post tests revealed the superiority of the dynamic condition over traditional glossing and the control group as regards the two types of L2 vocabulary knowledge.